Optimized Protocol for Subcutaneous Implantation of Encapsulated Cells Device and Evaluation of Biocompatibility - Audouard, Emilie; Rousselot, Lisa; Folcher, Marc; Cartier, Nathalie; Piguet, Françoise (Frontiers in Bioengineering and Biotechnology, 2021)
Improving a drug delivery system is critical to treat central nervous system disorders. Here we studied an innovative approach based on implantation of a wireless-powered cell-based device in mice. This device, coupling biologic material and electronics, is the first of its kind. The advantage of this technology is its ability to control the secretion of a therapeutic molecule and to switch the classical permanent delivery to activation on demand. In diseases with relapsing-remitting phases such as multiple sclerosis, such activation could be selectively achieved in relapsing phases. However, the safety (tolerance to biomaterials and surgical procedure) of such a clinical device needs to be verified. Therefore, the development of tools to assess the biocompatibility of the system in animal models is an essential step. We present the development of this new therapeutic approach, the challenges we encountered during the different steps of its development (such as cell loading in the chamber, surgery protocol for subcutaneous implantation of the device) and the tools we used to evaluate cell viability and biocompatibility of the device.